2005
DOI: 10.2174/1568015054863837
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of GABAA Receptors: Revived Interest in the Development of Subtype-selective Drugs

Abstract: Gamma-aminobutyric acid (GABA) is the most important inhibitory transmitter in the central nervous system. Most of the actions of GABA are mediated by GABAA receptors. These are choride ion channels that can be opened by GABA and can be modulated by a variety of pharmacologically and clinically important drugs. GABAA receptors are composed of five subunits that can belong to different subunit classes. So far, 19 different subunits have been identified in mammalian brain, exhibiting a distinct but overlapping r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 206 publications
(385 reference statements)
3
68
0
Order By: Relevance
“…Recent genetic studies with mice carrying a point mutation in α1, α2, α3 or α5 subunits have suggested a specifi c contribution of individual receptor subtypes to the spectrum of behavioral actions of these compounds [6]. These genetic advances have encouraged the synthesis and testing of new, selective BZ site ligands, that possess stronger affi nity and/or effi cacy profi les [7]. Here, we focus on α5-containing GABA-A receptors, as these receptors are highly expressed in brain regions substantially involved in memory formation and emotion [8][9][10].…”
Section: Research Articlementioning
confidence: 99%
“…Recent genetic studies with mice carrying a point mutation in α1, α2, α3 or α5 subunits have suggested a specifi c contribution of individual receptor subtypes to the spectrum of behavioral actions of these compounds [6]. These genetic advances have encouraged the synthesis and testing of new, selective BZ site ligands, that possess stronger affi nity and/or effi cacy profi les [7]. Here, we focus on α5-containing GABA-A receptors, as these receptors are highly expressed in brain regions substantially involved in memory formation and emotion [8][9][10].…”
Section: Research Articlementioning
confidence: 99%
“…The recent genetic studies with mice carrying a point mutation of histidine to arginine in α 1 , α 2 , α 3 or α 5 subunits, rendering the respective GABA A receptors selectively insensitive to effects of BZ site ligands, suggested a specific contribution of individual receptor subtypes to the spectrum of behavioral actions of these compounds . These genetic advances have encouraged synthesis of new, selective BZ site ligands, that possess affinity and/or efficacy profiles which enable separation of wanted from unwanted effects (Sieghart and Ernst, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…GABA A receptors belong to the superfamily of ligand-gated ion channels, along with nicotinic acetylcholine receptors, glycine receptors and 5-HT 3 receptors (1). They form heteropentameric chloride channels gated by GABA and modulated by several clinically relevant drugs, including benzodiazepines, barbiturates, neurosteroids, and ethanol (2)(3)(4). They are assembled for a large family of subunits (a1-6, b1-3, c1-3, d, e, p, and h in mammalian brain), of which 13 are expressed in the cerebellum (5).…”
Section: Introductionmentioning
confidence: 99%